STRATEGI PEMASARAN DAN PENGELOLAAN SUMBER DAYA MANUSIA DALAM MENINGKATKAN DAYA SAING UMKM DI KABUPATEN KERINCI - Enny Sestriyenti; Mohd. Pajri; Edwin Bustami (LPPM - STIE SAKTI ALAM KERINCI, 2025)
This study aims to analyze the influence of marketing strategies and human resource management on the competitiveness of Micro, Small, and Medium Enterprises (UMKM) in Kerinci Regency. The research uses a quantitative approach with data collected from UMKM actors in the region through surveys and interviews. Structural Equation Modeling (SEM) is employed to test the relationships between variables. The findings reveal that effective marketing strategies combined with well-managed human resources significantly improve UMKM performance, enhancing their market position and sustainability.